You are on page 1of 9

# 120 Chapter 8 General Solutions of Trigonometric Equations

## CHAPTER 8 8. 3 cos θ = 2 sin 2 θ − 3

Exercise 8A (p.186) 3 cos θ = 2 − 2 cos 2 θ − 3
2 cos 2 θ + 3 cos θ + 1 = 0
1. cos θ = −1 for 0° ≤ θ ≤ 180° (2 cos θ + 1)(cos θ + 1) = 0
θ = 180° 1
cos θ = − or cos θ = −1
2
− 3 π π 2π
2. 6 tan θ = for − < θ < θ = 2 nπ ± or θ = 2nπ ± π
2 2 2 3
− 3 where n is any integer.
tan θ =
12
θ = −0.14 (corr. to 2 d.p.) 9. 3 sec 2 θ = 4 tan θ
3 (1 + tan 2 θ) = 4 tan θ
3. sin θ = 0.28
3 + 3 tan 2 θ = 4 tan θ
θ = nπ + ( −1) n 0.28
3 tan 2 θ − 4 tan + 3 = 0
where n is any integer.
(tan θ − 3 )( 3 tan θ − 1) = 0
1
4. 3 tan θ = − 3 tan θ = 3 or tan θ =
3
− 3 π π
tan θ = θ = nπ + or θ = nπ +
3 3 6
π
θ = nπ − where n is any integer.
6
where n is any integer. 10. 6 tan θ = 5 csc θ
sin θ 5
6 =
1 cos θ sin θ
5. sin 3θ =
2 6 sin 2 θ = 5 cos θ
π 6 − 6 cos 2 θ = 5 cos θ
3θ = nπ + ( −1) n
4 6 cos 2 θ + 5 cos θ − 6 = 0
nπ n π
θ= + ( −1) (3 cos θ − 2)(2 cos θ + 3) = 0
3 12 2 3
cos θ = or cos θ = − (rejected)
where n is any integer. 3 2
θ = 2 nπ ± 0.84 (corr. to 2 d.p.)
π
6. tan(2θ − )= 3 where n is any integer.
4
π π 11. sin 5θ = cos 4θ
2θ − = nπ +
4 3 π
7π cos 4θ = cos( − 5θ)
2θ = nπ + 2
12 π
nπ 7π 4θ = 2 nπ ± ( − 5θ)
θ= + 2
2 24 π
4θ = 2 nπ + ( − 5θ)
where n is any integer. 2
π
9θ = 2 nπ +
7. 2 cos 2 θ + 3 cos θ + 1 = 0 2
2 π
(2 cos θ + 1)(cos θ + 1) = 0 θ = nπ + where n is any integer.
9 18
1 or
cos θ = − or cos θ = −1
2 π
4θ = 2 nπ − ( − 5θ)
2π 2
θ = 2 nπ ± or θ = 2nπ ± π π
3 −θ = 2 nπ −
where n is any integer. 2
π
θ = −2 nπ +
2
Chapter 8 General Solutions of Trigonometric Equations 121

2 π π 5π
Since the values of θ = nπ + include those θ = 2 nπ + or θ = 2 nπ +
9 18 12 12
π
of −2 nπ + , the general solution of the equation where n is any integer.
2
2 π
is θ = nπ + , where n is any integer.
9 18 15. sin 4θ + sin 2θ = 0
2 sin 3θ cos θ = 0
12. tan 4θ = cot 3θ
sin 3θ = 0 or cos θ = 0
π
tan 4θ = tan( − 3θ) π
2 3θ = nπ or θ = 2 nπ ±
π 2
4θ = nπ + − 3θ nπ π
2 θ= or θ = 2 nπ ± , where n is any integer.
π 3 2
7θ = nπ +
2
1 π tan θ + 3 cot θ = 5 sec θ
θ = nπ + 16.
7 14 sin θ 3 cos θ 5
+ =
where n is any integer. cos θ sin θ cos θ
sin 2 θ + 3 cos 2 θ = 5 sin θ
13. Let α be an acute angle such that tan α = 3 . Then sin 2 θ + 3 − 3 sin 2 θ = 5 sin θ
2 cos α = 1 2 sin 2 θ + 5 sin θ − 3 = 0
(2 sin θ − 1)(sin θ + 3) = 0
2 sin α = 3
π 1
α=
2
3 sin θ = or sin θ = −3 (rejected)
3 2
α π
The given equation becomes θ = nπ + ( −1) n
1 6
(2 cos α ) cos θ − (2 sin α )sin θ = 1
2(cos θ cos α − sin θ sin α ) = 1 where n is any integer.
1
cos(θ + α ) =
2
π π 17. sin 2 θ + 1 = 3 cos θ(sin θ + cos θ)
θ + = 2 nπ ± 2 sin 2 θ + cos 2 θ = 3 sin θ cos θ + 3 cos 2 θ
3 3
2π 2 tan 2 θ + 1 = 3 tan θ + 3
θ = 2nπ or θ = 2 nπ −
3 2 tan 2 θ − 3 tan θ − 2 = 0
where n is any integer. (2 tan θ + 1)(tan θ − 2) = 0
1
tan θ = − or tan θ = 2
2
14. Let α be an acute angle such that tan α = 1 . Then θ = nπ − 0.46 (corr. to 2 d.p.) or
2 cos α = 2 θ = nπ + 1.11 (corr. to 2 d.p.)
2 sin α = 2 2
2 where n is any integer.
π α
α=
4
2
The given equation becomes 18. cos 2θ = 3 cos θ + 4
2(sin θ + cos θ) =6 2 cos 2 θ − 1 = 3 cos θ + 4
2 sin θ + 2 cos θ = 3 2 cos 2 θ − 3 cos θ − 5 = 0
(2 sin α )sin θ + (2 cos α ) cos θ =
3 (2 cos θ − 5)(cos θ + 1) = 0
2(cos θ cos α + sin θ sin α ) =
3 5
cos θ = (rejected) or cos θ = −1
2
cos(θ − α ) =
3 θ = 2nπ ± π
2 where n is any integer.
π π
θ − = 2 nπ ±
4 6
122 Chapter 8 General Solutions of Trigonometric Equations

## 19. tan 3θ + sec 3θ = 1 When k = 2 n + 1 ,

sin 3θ π π
+
1
=1 + 2θ = (2 n + 1)π − − θ
cos 3θ cos 3θ 6 4
2n + 1 5π
sin 3θ + 1 = cos 3θ and cos 3θ ≠ 0 θ= π−
3 36
cos 3θ − sin 3θ = 1
π 2n + 1 5π
π ∴ θ = 2 nπ + or π−
2 cos(3θ + ) = 1 12 3 36
4
π 1 where n is any integer.
cos(3θ + ) =
4 2
π π
3θ + = 2 nπ ± π π
4 4 22. sin(θ − ) + 3 sin(θ + ) = 2
π 4 4
3θ = 2 nπ or 3θ = 2 nπ − π π π
2 sin(θ − ) + 3 sin( − + θ) = 2
2 2 π 4 2 4
θ = nπ θ = nπ −
3 3 6 1 π 3 π
The condition cos 3θ ≠ 0 means ∴ sin(θ − ) + cos(θ − ) = 1
2 4 2 4
π
3θ ≠ 2 nπ ± 1 2 3 2
2 Let r = ( ) + ( ) = 1 ,
2 π 2 2
θ ≠ nπ ± 1 3 π
3 6 r cos α = , r sin α = ,∴ α=
2 2 2 3
∴ θ = nπ , where n is any integer. π π π π
3 ∴ sin(θ − ) cos + cos(θ − )sin = 1
4 3 4 3
20. sin 2θ = cos 2θ − sin 2 θ + 1 π π
sin(θ − + ) = 1
4 3
2 sin θ cos θ = 2 cos 2 θ − sin 2 θ 5π
2 tan θ = 2 − tan 2 θ ∴ θ = 2 nπ + where n is any integer.
12
tan 2 θ + 2 tan θ − 2 = 0
(tan θ + 1)2 = 3
23. sin θ + sin 2θ + sin 3θ = 0
tan θ + 1 = ± 3 (sin 3θ + sin θ) + sin 2θ = 0
tan θ = −1 + 3 or tan θ = −1 − 3 2 sin 2θ cos θ + sin 2θ = 0
θ = nπ + 0.63 (corr. to 2 d.p.) or sin 2θ(2 cos θ + 1) = 0
θ = nπ − 1.22 (corr. to 2 d.p.) 2 cos θ + 1 = 0 or sin 2θ = 0
1
where n is any integer. cos θ = − or 2θ = nπ
2
2π nπ
21. 2 (cos θ + sin θ) = cos 2θ + 3 sin 2θ θ = 2 nπ ± or θ = , where n is any integer.
3 2
π π
2 [ 2 (sin cos θ + cos sin θ)]
4 4
π π
= 2 sin cos 2θ + 2 cos sin 2θ)] 24. sin 11θ sin 4θ + sin 5θ sin 2θ = 0
6 6 1 1
π π (cos 7θ − cos 15θ) + (cos 3θ − cos 7θ) = 0
∴ sin( + θ) = sin( + 2θ) 2 2
4 6 1
π π (cos 3θ − cos 15θ) = 0
∴ + 2θ = kπ + ( −1) k ( + θ) 2
6 4 sin 9θ sin 6θ = 0
where k is any integer.
sin 9θ = 0 or sin 6θ = 0
When k = 2 n , 9θ = nπ or 6θ = nπ
π π
+ 2θ = 2 nπ + + θ 1 1
6 4 θ = nπ or θ = nπ , where n is any integer.
π 9 6
θ = 2 nπ +
12
where n is any integer.
Chapter 8 General Solutions of Trigonometric Equations 123

## θ 3θ 29. (a) sin 4 x + cos 4 x

25. 4 cos cos =1
2 2 = sin 4 x + 2 sin 2 x cos 2 x
1
4 ⋅ (cos 2θ + cos θ) = 1 + cos 4 x − 2 sin 2 x cos 2 x
2
1
cos 2θ + cos θ =
1 = (sin 2 x + cos 2 x )2 − sin 2 2 x
2 2
1 2
1
2 cos θ − 1 + cos θ − = 0
2 = 1 − sin 2 x
2 2
4 cos 2 θ + 2 cos θ − 3 = 0 (b) 4(sin 4 x + cos 4 x ) − sin 2 x − 3 = 0
cos θ = 0.651 39 or −1.151 (rejected) 1
4(1 − sin 2 2 x ) − sin 2 x − 3 = 0 (by (a))
∴ θ = 2 nπ ± 0.86 (corr. to 2 d.p.) 2
where n is any integer. 2 sin 2 2 x + sin 2 x − 1 = 0
(sin 2 x + 1)(2 sin 2 x − 1) = 0
26. sin θ sin 7θ = sin 3θ sin 5θ ∴ sin 2 x = −1 or sin 2 x =
1
cos 6θ − cos 8θ cos 2θ − cos 8θ 2
=
n π π
2 2 2 x = nπ − ( −1) or 2 x = nπ + ( −1) n
∴ cos 6θ = cos 2θ 2 6
6θ = 2 nπ ± 2θ for any integer n. nπ n π nπ n π
∴ x= − ( −1) or + ( −1)
nπ nπ 2 4 2 12
θ= or θ =
2 4 where n is any integer.
nπ nπ nπ π
Since the values of θ = include those of , For x = − ( −1) n ,
4 2 2 4

the general solution of the equation is θ = , let n = 2 m
4
2 mπ π
where n is any integer. x= − ( −1)2 m
2 4
π π
27. cot θ + cot(θ + )=3 = mπ −
4 4
1 1 − tan θ let n = 2 m + 1
+ =3
tan θ 1 + tan θ (2 m + 1)π π
1 + tan θ + tan θ(1 − tan θ) = 3 tan θ(1 + tan θ) x= − ( −1)2 m +1
2 4
4 tan 2 θ + tan θ − 1 = 0 (2 m + 1)π π
tan θ = 0.390 4 or tan θ = −0.640 4 = +
2 4
θ = nπ + 0.37 or θ = nπ − 0.57 (2 m + 1)π π π
= − +
2 4 2
(corr. to 2 d.p.) (corr to 2 d.p.) π
where n is any integer. = ( m + 1)π −
4
28. sin 3 θ − cos3 θ = sin θ − cos θ π
∴ x = nπ −
(sin θ − cos θ)(sin θ + sin cos θ + cos θ)
2 2 4
= sin θ − cos θ π nπ π
∴ x = nπ − or x = + ( −1) n
(sin θ − cos θ)(1 + sin θ cos θ) = sin θ − cos θ 4 2 12
(sin θ − cos θ)(1 + sin θ cos θ) − (sin θ − cos θ) = 0 where n is any integer.
(sin θ − cos θ)sin θ cos θ = 0
sin θ − cos θ = 0 or sin θ cos θ = 0 1
tan θ = 1 or sin 2θ = 0 30. (a) [(sin x + cos x )2 − 1]
π 2
θ = nπ + or 2θ = nπ 1
4 = (sin 2 x + 2 sin x cos x + cos 2 x − 1)
n 2
θ= π 1
2 = (2 sin x cos x )
where n is any integer. 2
= sin x cos x
124 Chapter 8 General Solutions of Trigonometric Equations

## (b) Let t = sin x + cos x , Revision Exercise 8 (p.188)

∴ The given equation becomes 1. sec 5θ + csc 2θ = 0
1
t + (t 2 − 1) = 1 1 1
2 + =0
cos 5θ sin 2θ
t + 2t − 3 = 0
2
∴ − sin 2θ = cos 5θ
t = 1 or t = −3
π
∴ cos 5θ = sin( −2θ) = cos( + 2θ)
As sin x ≤ 1 and cos x ≤ 1, 2
∴ t = sin x + cos x = −3 is rejected. π
+ 2θ = 2 nπ ± 5θ , where n is any integer.
2
∴ sin x + cos x = 1 −2 nπ π 2 nπ π
π π 1 θ= + or θ = −
sin x cos + cos x sin = 3 6 7 14
4 4 2
2 nπ π 2 nπ π
π 1 ∴ θ= + or θ = −
∴ sin( x + ) = 3 6 7 14
4 2
π π
x + = nπ + ( −1) n 2. 3 + sin 2 x − sin x = 6 cos x
4 4
π 3 + 2 sin x cos x − sin x = 6 cos x
∴ x = nπ + [( −1) − 1] , where n is any
n
sin x (2 cos x − 1) + 3(1 − 2 cos x ) = 0
4
integer. (2 cos x − 1)(sin x − 3) = 0
1
cos x = or sin x = 3 (rejected)
31. (a) tan θ tan(θ + α ) = k 2
sin θ sin(θ + α ) π
⋅ =k x = 2 nπ ± , where n is any integer.
cos θ cos(θ + α ) 3
sin θ(sin θ cos α + cos θ sin α )
= k cos θ(cos θ cos α − sin θ sin α ) π π
3. 3 tan( x − ) = tan( x + )
sin θ cos α + sin θ cos θ sin α
2 12 12
π)
sin( x − 12 sin( x + 12π)
= k cos 2 θ cos α − k sin θ cos θ sin α 3⋅ =
cos( x − 12π) cos( x + 12π)
( k + 1)sin θ cos θ sin α
π π π π
= ( k cos 2 θ − sin 2 θ) cos α 3 sin( x − ) cos( x + ) = sin( x + ) cos( x − )
12 12 12 12
k +1 3 π 1 π
sin 2θ sin α (sin 2 x − sin ) = (sin 2 x + sin )
2 2 6 2 6
cos 2θ + 1 1 − cos 2θ sin 2 x = 1
= [k ( )− ]cos α
2 2 π
2 x = 2 nπ +
( k + 1)sin 2θ sin α 2
= ( k cos 2θ + k − 1 + cos 2θ) cos α π
x = nπ + , where n is any integer.
= [( k + 1) cos 2θ + ( k − 1)]cos α 4
∴ (1 − k ) cos α
= ( k + 1)(cos 2θ cos α − sin 2θ sin α ) 1
4. (a) 2 sin x cos( p − x ) = 2 ⋅ [sin p + sin(2 x − p)]
= ( k + 1) cos(2θ + α ) 2
= sin(2 x − p) + sin p
π (b) sin x + 2 sin x cos( p − x ) − sin p = 0
(b) Substitute α = , k = 2 into the result of (a),
3
∴ sin x + sin(2 x − p) + sin p − sin p = 0
π π
∴ 3 cos(2θ + ) = − cos
3 3 ∴ sin x + sin(2 x − p) = 0
π 1 sin(2 x − p) = sin( − x )
cos(2θ + ) = −
3 6 ∴ 2 x − p = nπ + ( −1) n ( − x )
π
2θ + = 2 nπ ± 1.738 [2 + ( −1) n ]x = p + nπ
3
6n − 1 ∴ p + nπ
θ= π ± 0.87 (corr. to 2 d.p.) x=
6 2 + ( −1) n
where n is any integer. where n is any integer.
Chapter 8 General Solutions of Trigonometric Equations 125

## 5. sin x + sin 2 x + sin 3 x + sin 4 x + sin 5 x = 0 2 π

(b) k = 3 , α = , ∴ tan α = 3
sin x + sin 5 x + sin 2 x + sin 4 x + sin 3 x = 0 3 3
2 sin 3 x cos 2 x + 2 sin 3 x cos x + sin 3 x = 0 2 3− 3 −1 3 1
sin 3 x (2 cos 2 x + 2 cos x + 1) = 0 tan θ = 3 2 = 3 =
1− 3 3 ⋅ 3 −1 3
sin 3 x = 0 or 2 cos 2 x + 2 cos x + 1 = 0 π
θ = nπ + , where n is any integer.
3x = nπ or 4 cos 2 x − 2 + 2 cos x + 1 = 0 6

x= or 4 cos 2 x + 2 cos x − 1 = 0
3 9. (a) Let c = cos 2 x ,
cos x = 0.309 or cos x = −0.809 1 − cos 2 x 1 − c
2π 4π ∴ sin 2 x = =
x = 2 nπ ± or x = 2 nπ ± 2 2
5 5 1 + cos 2 x 1 + c
cos x =
2
=
where n is any integer. 2 2
∴ (*) becomes
6. No solution is provided for the H.K.C.E.E. 1 − c 4 1 + c 4 17 2
( ) +( ) = c
question because of the copyright reasons. 2 2 16
1 − c 4 1 + c 4 17 2
(b) ( ) +( ) = c
7. (a) sin 2 x + sin 2 2 x + sin 2 3 x 2 2 16
1 − cos 2 x 1 − cos 4 x 1 − cos 6 x (1 − c) 4 + (1 + c) 4 = 17c 2
= + +
2 2 2 2c 4 − 5c 2 + 2 = 0
3 1 (c 2 − 2)(2c 2 − 1) = 0
= − (cos 2 x + cos 4 x + cos 6 x )
2 2 1
3 1 ∴ c 2 = 2 or c 2 =
= − (2 cos 2 x cos 4 x + cos 4 x ) 2
2 2
3 1 As c = cos 2 x , ∴ c = 2 is rejected.
2
= − cos 4 x (2 cos 2 x + 1)
2 2 2
∴ cos 2 x = ±
3 2
(b) sin 2 x + sin 2 2 x + sin 2 3 x = π π
2 2 x = 2 nπ ± or 2 x = (2 n + 1)π ±
3 4 4
sin 2 x + sin 2 2 x + sin 2 3 x − = 0 π 2n + 1 π
2
∴ x = nπ ± or x = ( 2 )π ± 8
1 8
− cos 4 x (2 cos 2 x + 1) = 0
2 where n is any integer.
cos 4 x (2 cos 2 x + 1) = 0
1
∴ cos 4 x = 0 or cos 2 x = − 10. (a) Let P(n) be the proposition
2
π 2π °ßsin θ − sin 3θ + sin 5θ + L
4 x = 2 nπ ±
or 2 x = 2 nπ ±
2 3 ( −1) n +1 sin 2 nθ
nπ π π + ( −1) n +1 sin(2 n − 1)θ = °®.
x= ± or x = nπ ± 2 cos θ
2 8 3 When n = 1 ,
for any integer n.
L.H.S. = sin θ
8. (a) sin(θ + α ) = k cos(θ − α ) ( −1)2 sin 2θ 2 sin θ cos θ
R.H.S. = = = sin θ
sin θ cos α + cos θ sin α 2 cos θ 2 cos θ
= k (cos θ cos α + sin θ sin α ) ∴ P(1) is true.
sin θ(cos α − k sin α ) Assume P(k) is true for any positive integer k.
= cos θ( k cos α − sin α ) i.e. sin θ − sin 3θ + sin 5θ + L
sin θ(1 − k tan α ) = cos θ( k − tan α ) +( −1) k +1 sin(2 k − 1)θ
k − tan α ( −1) k +1 sin 2 kθ
tan θ = =
1 − k tan α 2 cos θ
126 Chapter 8 General Solutions of Trigonometric Equations

Then 3
(c) sin 2θ =
sin θ − sin 3θ + sin 5θ + L + ( −1) k +1sin(2 k − 1)θ 2
+ ( −1) k +1+1 sin[2( k + 1) − 1]θ π
2θ = nπ + ( −1) n
k +1 3
( −1) sin 2 kθ
= + ( −1) k + 2 sin(2 k + 1)θ nπ n π
2 cos θ θ= + ( −1)
2 6
= [( −1) k +1 sin 2 kθ where n is any integer.
+ 2( −1) k + 2 sin(2 k + 1)θ cos θ] ÷ 2 cos θ
1 12 − 13. No solutions are provided for the H.K.C.E.E.
= {( −1) k +1 sin 2 kθ + 2( −1) k + 2 [sin 2 kθ questions because of the copyright reasons.
2
+ sin 2( k + 1)θ]} ÷ 2 cos θ
= [ −( −1) k sin 2 kθ + ( −1) k sin 2 kθ Enrichment 8 (p.190)
+ ( −1) k + 2 sin 2( k + 1)θ] ÷ 2 cos θ
1. (a) cos 4θ = 2 cos 2 2θ − 1
( −1)( k +1) +1 sin 2( k + 1)θ
= = 2(2 cos 2 θ − 1)2 − 1
2 cos θ
= 2( 4 cos 4 θ − 4 cos 2 θ + 1) − 1
Thus assuming P(k) is true for any positive integer
k, P( k + 1) is also true. By the principle of = 8 cos 4 θ − 8 cos 2 θ + 1
mathematical induction, P(n) is true for all
positive integers n. (b) 16 x 4 − 16 x 2 + 1 = 0
1
(b) sin θ cos θ − sin 3θ cos θ + sin 5θ cos θ 8x 4 − 8x 2 + = 0
2
+ L + sin 9θ cos θ = 0
Let x = cos θ
cos θ(sin θ − sin 3θ + sin 5θ + L + sin 9θ) = 0
1
cos θ = 0 (rejected) or cos 4θ − 1 + = 0
2
sin θ − sin 3θ + sin 5θ + L + sin 9θ = 0 cos 4θ =
1
( −1)5 +1 sin 2(5)θ
2
=0 π
2 cos θ 4θ = 2 nπ ±
3
sin 10θ = 0 for cos θ ≠ 0 nπ π
10θ = nπ θ= ±
2 12
nπ where n is any integer.
θ=
10 nπ π
x = cos( ± )
where n is any integer. 2 12
x = ±0.966, ± 0.259 (corr. to 3 sig.fig.)

## 11. (a) Sum of the roots = tan θ + cot θ

cos β cos(2α + β) + cos β
4 3 2. (a) 1 + m = 1 + =
= cos(2α + β) cos(2α + β)
3 2 cos(α + β) cos α
=
4 3 cos(2α + β)
(b) By (a), tan θ + cot θ = (b) (1 + m) tan α tan(α + β)
3
sin θ cos θ 4 3 2 cos(α + β) cos α sin α sin(α + β)
+ = = ⋅ ⋅
cos θ sin θ 3 cos(2α + β) cos α cos(α + β)
sin 2 θ + cos 2 θ 4 3 2 sin α sin(α + β)
= =
sin θ cos θ 3 cos(2α + β)
3 = 4 3 sin θ cos θ 2( − 12 )[cos(2α + β) − cos β]
=
3 = 2 3 sin 2θ cos(2α + β)
3 cos β − cos(2α + β)
sin 2θ = =
2 3 cos(2α + β)
3 cos β
= = −1
2 cos(2α + β)
= m −1
Chapter 8 General Solutions of Trigonometric Equations 127

π 3. tan θ = − 3
(c) Let α = x , β =
4 θ = tan −1 ( − 3 ) = −60°
cos π4
m= =5 k
cos(2 x + π4 )
By (b),
π
(1 + 5) tan x tan( x + ) = 5 −1 1
4
π 2
tan x tan( x + ) =
4 3 −180° −60° 180°
1 + tan x 2 θ
tan x ⋅ = −360° −270° −90° O 90° 270° 360°
1 − tan x 3
3 tan x + 3 tan 2 x = 2 − 2 tan x
3 tan 2 x + 5 tan x − 2 = 0 −1
(3 tan x − 1)(tan x + 2) = 0
1 − 3
tan x = or tan x = −2
3
x = nπ + 0.322 or x = nπ − 1.11
(corr. to 3 sig.fig.) Classwork 2 (p.181)
where n is any integer.
Principal General
value solution
Classwork 1 (p.178)
1
sin θ = 30° n
180°n + (−1) 30°
3 2
1. sin θ =
2 3
3 sin θ + =0 −60° 180°n − (−1)n60°
−1
θ = sin ( ) = 60° 2
2 1
k cos θ = − 120° 360°n ± 120°
2

1 1 1
tan θ + = 0 −56.3° 180°n − 56.3°
3 k = sin θ 3 2
2
θ
O 60° 90° 180° 270° 360° Classwork 3 (p.183)
1. sin θ + cos θ = 0
−1 sin θ = − cos θ
tan θ = −1
π
1 θ = nπ −
2. cos θ = − 4
2 where n is any integer.
1
θ = cos −1 ( − ) = 120°
2 2. 1 + 2 3 sin x cos x + 2 cos 2 x = 0
k
sin 2 x + cos 2 x + 2 3 sin x cos x + 2 cos 2 x = 0
1 sin 2 x + 2 3 sin x cos x + 3 cos 2 x = 0
1 k = cos θ (sin x + 3 cos x )2 = 0
2
120° sin x + 3 cos x = 0
θ
O 90° 180° 270° 360° sin x = − 3 cos x
1
− tan x = − 3
2
π
−1 x = nπ −
3
where n is any integer.
128 Chapter 8 General Solutions of Trigonometric Equations

## Classwork 4 (p.184) Classwork 7 (p.186)

tan 4 x − cot 3 x = 0 1 1
tan 4 x = cot 3 x cos 2θ cos 4θ = cos 6θ − cos 2θ
2 2
π
tan 4 x = tan( − 3 x ) 1 1 1
(cos 6θ + cos 2θ) = cos 6θ − cos 2θ
2 2 2 2
π
4 x = nπ + − 3 x 1 1
cos 2θ = − cos 2θ
2 2 2
nπ π cos 2θ = 0
x= +
7 14 π
2θ = 2 nπ ± , where n is any integer.
where n is any integer. 2
π
θ = nπ ±
4
Classwork 5 (p.184)

π π 1
cos cos θ − sin sin θ =
5 5 2
π 1
cos( + θ) =
5 2
π π
+ θ = 2 nπ ±
5 3
π π π π
∴ θ = 2 nπ + − or θ = 2 nπ − −
3 5 3 5
2π 8π
θ = 2 nπ + or θ = 2 nπ −
15 15

Classwork 6 (p.185)
1
Let α be an acute angle such that tan α = . Then,
2
1 = 5 sin α
2 = 5 cos α
α = 0.463 6
The given equation becomes
5 sin α sin θ − 5 cos α cos θ = 5
cos α cos θ − sin α sin θ = −1
cos(θ + α ) = −1
θ + 0.463 6 = 2 nπ ± π
= (2 n + 1)π
where n is any integer.
∴ θ + 0.463 6 = 2 nπ + π
θ = 2 nπ + 2.68 (corr. to 2 d.p.)